(untitled) (Third Sector Social Economic Review, 2022)
Academic studies on ""public relations researches"" have an important role in the field of public relations. The aim of this study is to explore how the publications in the public relations research field are differed in local and international journals. In order to look at the international literature, the publications indexed in the Web of Science (WoS) and in the Turkish literature, the studies indexed in the TR Index were chosen as a sample of this study. In both databases, the publications within the scope of the literature review searched with the keyword ""public relations research"", were analyzed bibliometric method within the scope of the research questions. Journals, authors, subject areas/keywords, universities, and countries which produced the most publications in the literature were examined and citation analysis were made. The datasets obtained from WoS and TR Index are handled separately due to the data structure differences in both databases. This study provides information on the data of the studies on ""public relations research"" in the international literature and the literature in Turkey. The subject of public relations research is an area which has been more significant and on which more research has been done in recent years. In both kinds of literature, it was determined that the most cited author was J.E. Grunig.